Analysis of Economic Efficiency of the Use of Production Factors in Soybean Farming (Glycine max (L.) Merrill) in Dam Village, Kedawung District Sragen Regency - Agung Prasetyo; Dewi Rahmawati Intan Permatasari; Ermareta Hanasya Rachman (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2026)
This study aims to determine the cost, revenue, and income of soybean farming and analyze the influence and efficiency of the use of production factors on soybean production in Dam Village, Kedawung District, Sragen Regency. The research method used is descriptive analytics with survey techniques. The research sample amounted to 30 farmers who were selected using the simple random sampling method. Production analysis uses the Cobb-Douglas production function. The results of the study showed that the cost of soybean farming was Rp8,210,872.27/Ha/MT, revenue was Rp10,026,073.81/Ha/MT, and income was Rp1,815,210.54/Ha/MT. Simultaneously, the factors of production of land area, labor, seeds, NPK Phonska fertilizer, Gandasil B fertilizer, and Dursban insecticide have a significant effect on soybean production. Partially, the area of land and seeds has a real effect, while other factors have no real effect. The use of production factors in soybean farming has not reached optimal economic efficiency.